Perumusan Strategi Business Model Canvas (BMC) Pada Rumah Tape Medan Tuntungan - Rahma; Nurlinda, Nurlinda; Novita, Vivianti (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2024)
This research will provide an overview of how a business model is built, so that MSMEs can obtain simple information to design a business model according to the product produced and according to the target market segment. The purpose of Business Model Canvas (BMC) planning is to obtain information about the best planning for productive partners if applied as appropriate technology and models in MSMEs. The long-term goal is to become literate among MSMEs on how to develop a business model concept that is easy, simple and complete. This research will also contribute to new MSME players in designing business models before building a business. So that potential risks can be discovered early and solutions can be found. This research is a qualitative research. The data collection technique was carried out using a combination of observation, interviews and FGG at the UMKM Rumah Tape Medan Tuntungan. The research results show that BMC can be used in designing business models for Tape House MSME entrepreneurs which have been running for some time.